Characteristics of Collagen-based Milkfish Bone Waste Extracted with Bromelain with Cofactor Ca2+ - Nasyanka, Anindi Lupita; Na’imah, Janatun; Firmani, Ummul; Octavia, Putri; Azizah, Viaristi Amelina (Jurnal Kefarmasian Indonesia, 2024)
Indonesian imports of gelatin and collagen raw materials totaled 4808 tons. Gresik is one of the producers of milkfish in East Java, with 87116 tons expected in 2022. Even though it contains type 1 collagen, milkfish bone waste that is not used at the center for making milkfish brains is an environmental hazard. Given this possibility, this study aimed to determine the qualitative characteristics of collagen extract from milkfish bone debris (Chanos chanos) with and without the addition of Ca2+ of varying quantities. The extraction method employs the enzyme bromelain 2% and cofactor metal ion Ca2+ (0.5%; 1.0%; 1.5%), which has previously been pre-treated in the form of defatting and deproteination, before determining physical and chemical properties. The results showed that using bromelain enzyme with Ca2+ boosted collagen yield. Adding 0.5% Ca2+ resulted in the highest yield, 7.58±1.88%. All collagen produced contains functional groups recognized in FTIR as type 1 collagen constituents (presence of amide A, amide B, amide I-III). The melting point of the collagen generated is between 144 and 157 °C. The SEM profile of collagen was porous sheets in all treatments. Except for the ash content, the chemical properties of collagen generated by adding the Ca2+ (pH 7.49-8.09; water content 7.75-8.15; ash content 6.56-7.78) fulfill SNI and BSP standards. Meanwhile, collagen synthesized without the inclusion of cofactors only meets the water content standards (pH 7.49-8.09; water content 7.75-8.15; ash content 6.56-7.78). The demineralization stage is required to produce milkfish bone debris before extraction to achieve these requirements.